Czynniki rozwoju firm pośrednictwa kredytowego w Polsce - Półtorak, Bogusław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper discusses basic determinants of credit intermediaries' functioning in Poland. The author describes market, economic, and legal conditions in terms of traditional intermediation and via Internet as well. The outsourcing of credit services can be deepened as a result of market liberalization and internationalization. Additionally, the inclusion of the definition of bank operations outsourcing into the Polish Banking Act created an institutional framework for credit intermediation and accelerated its development. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 322-331